“MARGANEC TOPARSHASÍ ELEMENTLERI” TEMASÍN ÚYRENIWDE INTERAKTIV USÍLLARDAN PAYDALANÍW - Kamalova, M.O.; Aytbaeva, X.B.; Aymurzaeva, L.G. (SCIENCE and SOCIETY, 2024)
This article presents the authors’ works and suggestions on organizing classes using the "Why and How" scheme in chemistry lessons. These methods enhance students’ creativity and activity.